Advances in medical management of acute liver failure in children: promoting native liver survival. (October 2022) - Deep, Akash; Alexander, Emma C; Bulut, Yonca; Fitzpatrick, Emer; Grazioli, Serge; Heaton, Nigel; Dhawan, Anil
Summary: Paediatric acute liver failure (PALF) is defined as a biochemical evidence of acute liver injury in a child with no previous history of chronic liver disease characterised by an international normalised ratio (INR) of 1·5 or more unresponsive to vitamin K with encephalopathy, or INR of 2·0 or more with or without encephalopathy. PALF can rapidly progress to multiorgan dysfunction or failure. Although the transplant era has substantially changed the outlook for these patients, transplantation itself is not without risks, including those associated with life-long immunosuppression. Consequently, there has been an increased focus on improving medical management to prioritise bridging of patients to native liver survival, which is possible due to improved understanding of the underlying pathophysiology of multiorgan involvement in PALF. In this Review, we discuss recent advances in the medical management of PALF with an aim of reducing the need for liver transplantation. The Review will focus on the non-specific immune-mediated inflammatory response, extracorporeal support devices, neuromonitoring and neuroprotection, and emerging cellular and novel future therapeutic options.